Correlation of the cognitive illusion of age with well-being in adolescence - A.R. Novikova; Y.A. Sychenko (Психолого-педагогические исследования)
Context and Relevance. This article considers one possible correlate of well-being, the cognitive illusion of age. A number of studies have shown the correlation of cognitive illusions of age with either subjective well-being or psychological well-being, studying it in samples with significant age variation. Objective. To identify the correlation of the cognitive illusion of age with both subjective and psychological well-being of individuals in adolescence and to establish the variables mediating this correlation. Hypotheses. Indicators of subjective and psychological well-being are hypothesized to be significantly higher in adolescents with a negative cognitive illusion of age compared to those with a positive cognitive illusion. Sex and employment are hypothesized to mediate the relationship between the cognitive illusion of age and both subjective and psychological well-being. Methods and Materials. The sample consisted of 96 students (M = 19,27, SD = 0,814, where 48% were young men) aged between 18 and 21 years. The following methods were used: “Age-of-me” (B. Barak); “Life Satisfaction Scale” (E. Diener); “Positive and Negative Affect Schedule” (D. Watson, L. Clark, A. Tellegen); “Ryff's Scales of Psychological Well-being”. Results. The study found that subjective age overestimation (negative cognitive illusion of age), as opposed to positive cognitive illusion, is correlated with higher indicators of psychological and subjective well-being of a person in adolescence. The hypothesis that sex and employment mediate the correlation between the cognitive illusion of age and well-being was tested. It was found that regardless of sex and work experience, negative cognitive illusion was directly related to higher measures of well-being in young adulthood. Conclusions. The results suggest that the negative cognitive illusion of age may contribute to higher levels of both psychological and subjective well-being in adolescence.